Kinetic study of HTPB (Hydroxyl Terminated Polybutadiene) Synthesis Using Infrared Spectroscopy - Heri Budi Wibowo; Widhi Cahya Dharmawan; Ratih Sanggra Murti Wibowo; Adi Yulianto (Universitas Gadjah Mada, 2020)
A kinetic study of HTPB synthesis by radical polymerization of butadiene with hydrogen peroxide initiator was conducted using infrared spectroscopy. HTPB conversion was determined based on the conjunction termination rate constant, and all polymerization kinetics were evaluated to identify the constant. All polymerization steps (decomposition, initiation, propagation, conjunction, and proportional termination) can be evaluated based on polymer conversion and functionality from data provided by infrared spectroscopy. The investigation variables included the initial molar ratio of initiator to monomer (H2O2/butadiene) and the reaction temperature. These steps were assumed as the first-order reactions, giving constant reaction rates of kd, ka, kp, kt, ktc, and ktd. The reaction rates obtained for these constants were 4.2 × 10–5 sec–1, 8.9 × 10–4, 7.7 × 103, 8.5 × 107, 3.2 × 107 and 5.3 × 107 L mol–1 sec–1, respectively, with activation energy of 7608, 14188, 2247, 105, 87 and 135 kJ mol–1, respectively. The determining step of the reaction rate was identified as the initiation reaction. HTPB conversion can be measured if all polymerization kinetics constants have been evaluated.